State of thermal tolerance in an endangered himalayan fish Tor putitora revealed by expression modulation in environmental stress related genes - Amarjit Kaur; Shahnawaz Ali; Onkar Singh Brraich; C. Siva; Pramod Kumar Pandey (Scientific Reports, 2025)
Abstract Increasing temperature due to global warming in the Himalayan regions has severe implications for the survival of aquatic ectotherms. To study the thermal acclimation and heat tolerance of an endangered Himalayan fish species, Tor putitora, we examined tissue-specific mRNA expression patterns of heat-shock proteins (HSP90β; HSP70, HSP60, HSP47, HSP30, and HSP20), warm-temperature acclimation proteins (WAP65-1) and cyclin-dependent kinase inhibitor 1B (CDKN1B) genes in liver, brain, gill, kidney, muscle, and gonad tissues at the intervals of 10, 20, and 30 days during a high-temperature treatment (34.0 °C) for 30 days. All the tested genes have exhibited tissue-specific and time-dependent expression patterns. Heat shock proteins’ differential expression and modulation across examined tissues indicate their role in long-term cellular adaptation, protection against the cytotoxic effect of hyperthermia, and species acclimation to higher temperatures. WAP65-1 and CDKN1B expression in treatment groups suggests its involvement in maintaining homeostasis, long-term temperature acclimation, and thermotolerance during chronic thermal exposure. The response of studied genes under heat stress indicates their potential use as environmental stress biomarkers in this species. The present study elucidates molecular mechanisms regulating the thermal acclimation capacity and thermotolerance of T. putitora and its survival under future projections of widespread warming in the Himalayan region.